Juvenile crime - Hamilton, Jill. (Detroit : Greenhaven Press, 2009)
From the Publisher's Website: Behind policy debate over welfare reform, AIDS funding and hate crime laws are people struggling with poverty, illness and discrimination. Illuminating the often-neglected human side of society's pressing problems, this must-have series broadens and balances readers' exposure to issues such as homosexuality, poverty and suicide. Each anthology presents a diverse collection of personal narratives written by individuals with first-hand experience in the topic being discussed, either as a participant, a witness or an involved professional. Gangs, for example, include the perspectives of gang members as well as those who have encountered gang violence and those who have counseled gang members. Each volume in Social Issues Firsthand offers a thorough bibliography for future research, plus a list of related organizations to contact and a detailed index enabling quick access to target information.
Foreword -- Introduction -- Chapter 1: Reasons For Turning To Crime -- 1: My life as a drug dealer / Ariel Corporan as told to Stacy Abramson -- 2: Foster care, mental health facilities, and the juvenile justice system / Roger Weisberg and Vansessa Roth -- 3: I was a gang member / Yovani Whyte as told to Stacy Abramson -- 4: My life in crime: four young people speak out / Mark Johnson -- Chapter 2: Punishments and Other Consequences -- 1: Doing time in Los Angeles day camps / LA Youth -- 2: My son got help, not jail / Anonymous -- 3: Trouble with tough love / Maia Szalavitz -- 4: My brother was shot / Ayesha -- Chapter 3: Others Affected By Juvenile Crime -- 1: Career in juvenile corrections / Francisco "Frank" J Alarcon, Jr -- 2: Student threatened my school on the internet / Allison Ko -- 3: Teaching a writing class at a juvenile detention center / Kim Antieau -- Organizations to contact -- For further research -- Index.
"A part of Gale, Cengage Learning."
Includes bibliographical references (p. 79-82) and index.
Keywords: Juvenile delinquency -- United States; Juvenile delinquency -- United States -- Juvenile literature; Juvenile delinquents -- United States; Juvenile delinquents -- United States -- Juvenile literature; Juvenile corrections -- United States; Juvenile corrections -- United States -- Juvenile literature